2015
DOI: 10.1007/s00221-015-4527-y
|View full text |Cite
|
Sign up to set email alerts
|

Delayed grip relaxation and altered modulation of intracortical inhibition with aging

Abstract: Grip relaxation is a voluntary action that requires an increase in short-interval intracortical inhibition (SICI) in healthy young adults, rather than a simple termination of excitatory drive. The way aging affects this voluntary inhibitory action and timing of grip relaxation is currently unknown. The objective of this study was to examine aging-related delays in grip relaxation and SICI modulation for the flexor digitorum superficialis (FDS) muscle during grip relaxation. The main finding was that young adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…This may be indicative of plastic or physiological changes regarding the availability and transmission of the neurotransmitter GABA, or the action of baclofen that facilitates GABAB activity [3,6] . However, these inhibitory networks are speculated to play a role in movement regulation and behavior in both healthy and diseased states [18][19][20][21][22] . These inferences, together with novel information obtained in our recent study [7] , allow for interpretation of how intracortical inhibition is linked to some of the motor symptoms that are prominent following SCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be indicative of plastic or physiological changes regarding the availability and transmission of the neurotransmitter GABA, or the action of baclofen that facilitates GABAB activity [3,6] . However, these inhibitory networks are speculated to play a role in movement regulation and behavior in both healthy and diseased states [18][19][20][21][22] . These inferences, together with novel information obtained in our recent study [7] , allow for interpretation of how intracortical inhibition is linked to some of the motor symptoms that are prominent following SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SICI is likely to influence cortical mechanisms governing force gradation and deficits to this circuit in SCI [7] may contribute to impaired precision performance and submaximal force control. Further, impaired precision control seen in SCI may be due to the influence that reduced SICI has on voluntary muscle relaxation [16,22] . A recent study in aging populations revealed that, in contrast to young healthy individuals, older adults did not show increases in SICI with voluntary grip relaxation and had longer grip relaxation times.…”
Section: Alterations To Motor Behavior In Spinal Cord Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Because the phase duration of ascent was similar between groups, this early activation in hip stabilizers is indicative of a trunk strategy to older adults keep up with the metronome. We interpret the age-specific 37% longer activation of the five muscle groups combined (Figure 4) as an inability to relax muscles after force generation (Motawar et al, 2016). We conjecture that the lower MVIF, over-activation in dorsiflexor's RMS-amplitude and longer muscle activation duration in older vs. younger are related to the dramatically fewer number of STS trials (Table 1), and indeed an additional correlation confirmed this (r range = −0.51 to −0.66, all p < 0.01, details at Supplementary Material 2).…”
Section: Effects Of Age On Muscle Activation During Sts Before Rstsmentioning
confidence: 94%
“…Indeed, in a number of activities of daily living, not only do the prime agonists but the antagonists also become over-activated resulting in the age-typical agonist-antagonist co-activation (Hortobágyi et al, 2003 ; Bautmans et al, 2011 ; Bryanton and Bilodeau, 2017 ; Chandran et al, 2019 ). Such an activation pattern is also associated with impaired excitatory and inhibitory control of muscle contraction and relaxation (Motawar et al, 2016 ) that can reduce power generation in old age (Clark et al, 2010 ). Imaging and magnetic brain stimulation studies suggest that age-specific imbalances in excitatory-inhibitory corticospinal circuits and cortical over-activation can accompany higher muscle activation and delay muscle relaxation (Hortobágyi and Devita, 2006 ; Motawar et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%